Hydrothermal carbonization of date palm pits and pine nut shells: fuel characteristics of hydrochar, and surface characteristics and adsorption application of activated hydrochar - Bedoui, Amina; Nouri, Hanen; Boutaieb, Mouzaina; Ghouil, Riheb; Ledesma, Beatriz; Alonso, Maria; Roman, Silvia; Guiza, Monia (Comptes Rendus. Chimie, 2025)
This work aimed at producing hydrochars (HCs) from agricultural waste to investigate their potential as solid fuels and, following physical activation, as precursors of activated carbon. Date palm pits (DPPs) and pine nut shells (PNSs) were hydrothermally carbonized at 250 °C for 1 h in various solid/water ratios (1:8; 1:12, and 1:48). The derived HCs were then activated at 850 °C using steam (1 h; 70 vol% H2O in N2). The impact of the solid/liquid ratio and the type of biomass on HC properties was highlighted. Fuel characteristics of HC were examined via ultimate analysis, higher heating value (HHV), and solid yield. Surface characterization was determined by several analytical techniques, including N2 adsorption (N2), X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. The solid/water ratio had no significant effect on HC characteristics. As fuel, all HCs had high carbon content (%C) and HHV. Their calculated H/C and O/C ratios determined on the HCs showed improved stability as fuels. The HC from DPP with solid/water ratio 1:48 had the highest HHV (29.7 MJ/kg). The PNS HC had the highest mass yield of 48%. Textural properties showed a significant number of oxygen groups and a low specific surface area. Activated HCs demonstrated high Brunauer–Emmett–Teller surface areas (857 and 827 m2/g for DPP and PNS, respectively) and high total pore volumes (0.582 and 0.541 cm3/g for DPP and PNS, respectively). Thus, the energetic properties of the HC show its potential to be used as solid fuel while the textural qualities of the activated HC demonstrate its high adsorbent ability.